Amino acid depletion as a means of cancer treatment: a rebirth of an old treatment paradigm - Cheng, P. N.M. (Progress in Nutrition, 2010)
Summary Nutritional deprivation/depletion studies in laboratory/veterinary animals have led to great scientific discoveries and better understanding of the biosyntheses and metabolisms of the studied nutrients, such as fatty acids, vitamins, amino acids and hormones. In cancer cell cultures, depletion of a number of amino acids such as arginine, 5-hydroxytryptophan, leads to cell death in a broad range of cancer cells. This provides the scientific basis of amino acid depletion in cancer treatment. La deplezione di aminoacidi come mezzo per il trattamento del cancro: la rinascita di un vecchio paradigma di trattamento Riassunto Studi di deplezione/deprivazione nutrizionale in animali di laboratorio e animali sottoposti a cure veterinarie hanno portato a grandi scoperte scientifiche e a una migliore comprensione della biosintesi e del metabolismo dei nutrienti studiati, come gli acidi grassi, le vitamine, gli aminoacidi e gli ormoni. In colture di cellule cancerose, l’esaurimento di un certo numero di aminoacidi come l’arginina, 5-idrossitriptofano, porta alla morte cellulare in una vasta gamma di cellule tumorali. Ciò fornisce la base scientifica della deplezione di aminoacidi nel trattamento del cancro.